Fortification of pasta with upcycled bread and plant-based powder blends - Najeebah Az-Zahra Tashim; Syazana Abdullah Lim; Aida Maryam Basri (Discover Food)
Abstract Food waste remains a significant global challenge for sustainability, leading to the concept of a circular economy. To support this concept, the objective of this study was to develop value-added pasta from unsold wholemeal bread and low glycemic index (GI) bread and to incorporate mixed plant powders (Polygonum minus + Amaranthus tricolor, Polygonum minus + Apium graveolens and Polygonum minus + Breynia androgyna) that could provide additional nutritional and health benefits. The in vitro antioxidant potential, cooking quality, texture and sensory properties of fortified wholemeal bread pasta and low-GI bread pasta samples were evaluated and compared. The results revealed that the incorporation of bread and plant powders substantially increased the antioxidant capacity of cooked samples enriched with low-GI pasta, up to 77.2% in DPPH and 0.40 mg/g AAE in terms of ABTS radical scavenging activity, 0.31 mg/g AAE in terms of FRAP reducing ability, 0.27 mg/g GAE in total phenolic content, 0.75 mg/g QE in total flavonoid content and 0.27 mg/g QE in total flavonol content, in comparison with the control pasta. The inclusion of bread and plant powder also altered the textural properties of fortified pasta. In particular, low-GI bread pasta fortified with plant powders presented increased chewiness (2.91–3.31 g mm) and springiness (0.84–0.89 mm) values compared with those of the control pasta, although their cooking and sensory properties were not significantly influenced. These results indicate that the development and fortification of pasta through the upcycling of breads and mixed plant powders is a valuable approach for producing sustainable bread pasta with potential health-promoting effects.